TERRORISM, DEMOCRACY AND GLOBAL SECURITY - Arowolo, Dare E. (European Scientific Journal, ESJ, 2013)
The need for peaceful coexistence among the nations of the world has been the pursuit of world leaders. This desire is constantly being threatened by terrorism. There are differing opinions on whether democracy can minimise terrorism. The school of thought that believes that democracy can influence terrorism hinges its argument on the opportunities and freedoms that democracy offers: democracy provides opportunities for conflict prevention, conflict management and conflict resolution as well as opportunities of political participation. The other school of thought argues that there is no empirical evidence for a strong link between democracy, or any other regime type, and terrorism, in either a positive or a negative direction. Terrorism, it insists, springs from sources other than form of government. The paper, however, presented the two arguments and concluded that while democracy may not be able to eliminate terrorism, it is, however, capable of minimising it through exclusive adherence to the tenets of democracy. Using content analysis, the paper determined the extent of impact of democracy on terrorism and the implication of terrorism on global security.